Programa Água para Todos: análise dos efeitos da qualidade da água na redução da mortalidade infantil - Barbosa, Leonardo de Frias (2019)
This study aims to study the water quality effects of the Water for All Program (PAPT), in the reduction of infant mortality in children from zero to four years old, in rural communities of the northeastern region of the state of Piauí. The Water for All Program, aimed at the human development and food security of families in situations of social vulnerability, provided the installation of cisterns, making universal access to water available to communities in rural areas. The database used in this study consists of 224 municipalities in the state of Piauí in the period from 2010 to 2015. Through the models for panel data the results show that the model that best fitted the data is the fixed effects model. The results show that there is evidence that the improvement in the water quality of the program reduces the number of preventable deaths.